2014
DOI: 10.1186/1748-5908-9-80
|View full text |Cite
|
Sign up to set email alerts
|

Design, implementation, and evaluation of a knowledge translation intervention to increase organ donation after cardiocirculatory death in Canada: a study protocol

Abstract: BackgroundA shortage of transplantable organs is a global problem. There are two types of organ donation: living and deceased. Deceased organ donation can occur following neurological determination of death (NDD) or cardiocirculatory death. Donation after cardiocirculatory death (DCD) accounts for the largest increments in deceased organ donation worldwide. Variations in the use of DCD exist, however, within Canada and worldwide. Reasons for these discrepancies are largely unknown. The purpose of this study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Both the TDF and BCT Taxonomy (v1), however, are becoming increasingly popular for understanding clinical behaviour and guiding implementation intervention design “from scratch”. Examples of published work using the TDF and BCT Taxonomy to guide quality improvement are seen in antibiotic prescribing [ 30 ] and organ donation [ 31 ], but to the authors’ knowledge, they have not yet been used in the design of interventions to improve implementation sepsis guidelines. In addition, as far as we are aware, this is the first example of a study that has used these tools to “enhance” an existing pragmatically developed intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the TDF and BCT Taxonomy (v1), however, are becoming increasingly popular for understanding clinical behaviour and guiding implementation intervention design “from scratch”. Examples of published work using the TDF and BCT Taxonomy to guide quality improvement are seen in antibiotic prescribing [ 30 ] and organ donation [ 31 ], but to the authors’ knowledge, they have not yet been used in the design of interventions to improve implementation sepsis guidelines. In addition, as far as we are aware, this is the first example of a study that has used these tools to “enhance” an existing pragmatically developed intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The BCT Taxonomy (v1) has also been used to identify active ingredients in other existing implementation interventions. Both tools have been used to inform the design of various implementation interventions in healthcare settings [ 30 , 31 ]. In the current study, an existing pragmatically designed quality improvement programme, which had achieved some level of success, was already ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…One systematic review by Laba and colleagues [ 32 ] used both the Behaviour Change Wheel and an earlier version of the BCT Taxonomy to classify strategies used to improve adherence to cardiovascular medications across 14 studies [ 33 ]. Examples of using the BCT Taxonomy to guide intervention development on the basis of TDF analyses are seen in antibiotic prescribing [ 34 ] and organ donation [ 35 ]. A common scenario in clinical practice is that of having interventions in place which have achieved some level of success, but are not fully reported or understood and may require improvement.…”
Section: Introductionmentioning
confidence: 99%
“…This study further demonstrated the usefulness of using a behavioural analysis approach to identify the behavioural content of interventions and assess how well these address the barriers to desired behaviour change. A number of studies showed the strengths of such approaches in other contexts [ 48 , 49 , 50 ]. We built on this theoretical approach by focusing on interventions which had shown to be effective research at changing the target behaviours and consulting expert stakeholders to develop new intervention components.…”
Section: Discussionmentioning
confidence: 99%
“…We used the Behaviour Change Wheel (BCW), Theoretical Domains Framework (TDF) and the 93-item taxonomy of Behaviour Change Techniques (BCTTv1) to describe the behavioural content of interventions. The BCW enables characterisation of interventions using nine intervention functions, i.e., purposes that an intervention may serve; and seven policy categories, i.e., channels through which interventions are implemented [ 4 , 48 ] The TDF is an integrative framework of 14 theoretical domains of influences on behavior [ 49 ]. Behaviour change techniques (BCTs) are defined as active ingredients of interventions designed to bring about change [ 50 ].…”
Section: Methodsmentioning
confidence: 99%